Role of surgical hyoid bone repositioning in modifying upper airway collapsibility - Samaha, Corine J.; Tannous, Hiba J.; Salman, Diane; Ghafari, Joseph G.; Amatoury, Jason (Frontiers in Physiology, 2022)
Background: Surgical hyoid bone repositioning procedures are being performed to treat obstructive sleep apnea (OSA), though outcomes are highly variable. This is likely due to lack of knowledge regarding the precise influence of hyoid bone position on upper airway patency. The aim of this study is to determine the effect of surgical hyoid bone repositioning on upper airway collapsibility. Methods: Seven anaesthetized, male, New Zealand White rabbits were positioned supine with head/neck position controlled. The rabbit’s upper airway was surgically isolated and hyoid bone exposed to allow manipulation of its position using a custom-made device. A sealed facemask was fitted over the rabbit’s snout, and mask/upper airway pressures were monitored. Collapsibility was quantified using upper airway closing pressure (Pclose). The hyoid bone was repositioned within the mid-sagittal plane from 0-5mm (1mm increments) in anterior, cranial, caudal, anterior-cranial (45°) and anterior-caudal (45°) directions. Results: Anterior displacement of the hyoid bone resulted in the greatest decrease in Pclose amongst all directions (p=0.002). Pclose decreased progressively with each increment of anterior hyoid bone displacement, and down by -3.98 ± 1.31 cmH2O at 5mm. Cranial and caudal hyoid bone displacement did not alter Pclose (p>0.35). Anterior-cranial and anterior-caudal hyoid bone displacements decreased Pclose significantly (p<0.004) and at similar magnitudes to the anterior direction (p>0.68). Conclusion: Changes in upper airway collapsibility following hyoid bone repositioning are both direction and magnitude dependent. Anterior-based repositioning directions have the greatest impact on reducing upper airway collapsibility, with no effect on collapsibility by cranial and caudal directions. Findings may have implications for guiding and improving the outcomes of surgical hyoid interventions for the treatment of OSA.